2013
DOI: 10.1371/journal.pone.0069424
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of MAPK/NF-κB Signaling in the Activation of the Cholinergic Anti-Inflammatory Pathway in Experimental Colitis by Chronic Vagus Nerve Stimulation

Abstract: BackgroundAutonomic nervous system dysfunction is implicated in the etiopathogenesis of inflammatory bowel diseases (IBD). Therapies that increase cardiovagal activity, such as Mind-Body interventions, are currently confirmed to be effective in clinical trials in IBD. However, a poor understanding of pathophysiological mechanisms limits the popularization of therapies in clinical practice. The aim of the present study was to explore the mechanisms of these therapies against 2,4,6-trinitrobenzenesulfonic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(137 citation statements)
references
References 63 publications
6
129
1
1
Order By: Relevance
“…In animal models, VNS has been evaluated as a therapy in various diseases, such as sepsis, hemorrhagic shock, IBD, IRI in brain and heart, and arthritis (11,20). In rats, α7nAChR agonists reduce kidney IRI (21), but the effect of VNS on kidney injury and the underlying mechanisms have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…In animal models, VNS has been evaluated as a therapy in various diseases, such as sepsis, hemorrhagic shock, IBD, IRI in brain and heart, and arthritis (11,20). In rats, α7nAChR agonists reduce kidney IRI (21), but the effect of VNS on kidney injury and the underlying mechanisms have not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of VNS may reach beyond its established roles in intractable epilepsy and treatment-resistant depression [36,37]. There is experimental evidence for the use of VNS in inflammatory conditions, particularly rheumatoid arthritis [38,39] and IBD [40,41]. However, prospective controlled trials are pending.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, p38 MAPK triggers the transcriptional activation of NF-κB via the phosphorylation of p65 (Kefaloyianni et al, 2006;Shin et al, 2011a). Furthermore, the activity of p38 MAPK is higher in IBD patients than in normal controls (Vallabhapurapu and Karin, 2009) and phosphorylated p38 MAPK levels were reported to be elevated in experimental colitis model (Sun et al, 2013). Interestingly, immunohistochemical analysis of the inflamed mucosal biopsies of IBD patients showed that p38 MAPK and NF-κB were mainly localized in lamina propria macrophages and neutrophils (Luhrs et al, 2002;Waetzig et al, 2002).…”
Section: Discussionmentioning
confidence: 99%